Relationship between serum lipopolysaccharide binding protein levels, disease activity, and clinical characteristics in Paraguayan patients with systemic lupus erythematosus. (November 2021) - Losanto, Jhonatan; Langjahr, Patricia; Barrios, Graciela; Paats, Astrid; Acosta de Hetter, María E; de Guillén, Ivalena; Duarte, Margarita; Acosta-Colman, Isabel; Cervera, Ricard
Introduction: Systemic exposure to bacterial components like lipopolysaccharide (LPS) is among the non-genetic factors that could be involved in the onset or progression of systemic lupus erythematosus (SLE). Lipopolysaccharide-binding protein (LBP) participates in the recognition of LPS and in the inflammatory response. Here, we investigated LBP in SLE patients and its relationship with disease activity and SLE phenotypes. Methods: Eighty-one adult patients with SLE from IMID-PY biobank (Paraguay) were included in the study. The clinical and laboratory variables were used to determine SLE activity. LBP levels were determined by ELISA in SLE patients and age- and sex-matched population-based controls. Results: Patients with SLE have lower levels of circulating LBP compared to healthy controls ( p = 0.0007). No significant correlation was found between serum LBP levels and disease activity. A significant difference was observed in LBP levels with regard to the presence of arthritis ( p = 0.026). No other relation was found with clinical parameters. Conclusions: We found low levels of LBP in SLE patients compared to the control group. No correlation was detected between LBP levels and disease activity. It would be interesting for future studies to evaluate the impact of low levels of LBP on lupus immunopathogenesis.